Exploring Inequality in Relation to Rates of Reporting Sexual Assault at Canadian Post-Secondary Institutions - Taylor Kylie MacKenzie (Canadian Society for Studies in Education, 2018)
Abstract: Sexual assault on Canadian post-secondary campuses remains a persistent, reoccurring issue, with 25% of post-secondary women being sexually assaulted (Hawn et al., 2018). This examination of the literature endeavours to determine how the policies, barriers, and responses to sexual assault at Canadian post-secondary institutions helps or hurts an individual's odds of reporting sexual assault issues. The literature review revealed three themes that act as obstacles to reporting sexual assault: a) lack of sexual assault policies, b) existing barriers to support, and c) poor responses by post-secondary institutions. If these obstructions are reduced-or eliminated completely in a best-case scenario-the likelihood of sexual assault survivors reporting may increase.